(untitled) (Revista Investigación & praxis en CS Sociales, 2024)
This research project aims to foster the cultural identity of the community in the Navarro hamlet, Pamplona, Norte de Santander, through local history as a cross-cutting axis. Using a qualitative and participatory approach, strategies are developed to rescue traditions, narratives, and cultural elements that shape the identity of its inhabitants. The project is divided into three phases: identifying key cultural aspects, designing an educational strategy based on local history, and implementing activities to strengthen the community’s sense of belonging. The results demonstrate a positive community response, highlighting the value of local history as a tool for revitalizing cultural identity and promoting social cohesion. Additionally, the project culminates in the creation of a final product that documents shared knowledge and experiences, ensuring the preservation of local wisdom for future generations. This tangible legacy reflects the community’s commitment to safeguarding its cultural heritage.